(untitled) (Journal of Informatics Education and Research, 2025)
The rapid advancement of mobile payment systems has revolutionized e-commerce, transforming the banking and retail sectors by enhancing convenience, security, and accessibility. This study explores the integration of advanced AI-driven technologies, particularly federated learning, in mobile payment systems to ensure robust data privacy and optimize transaction efficiency. Federated learning enables real-time, secure data processing across multiple devices without compromising user confidentiality. This paper also examines tools like Stripe Radar, a cutting-edge fraud detection and prevention system powered by AI, that complement mobile payment platforms by safeguarding transactions in the dynamic e-commerce landscape. The findings emphasize the pivotal role of mobile payment systems in fostering digital financial inclusion and driving the global transition towards a cashless economy.